Challenges to promote the ecosystem approach to beach management in Latin America and the Caribbean - Corrêa, Marina Ribeiro; Xavier, Luciana Yokoyama; Gonçalves, Leandra R.; Andrade, Mariana Martins de; Oliveira, Mayara de; Malinconico, Nicole; Botero, Camilo M.; Milanés, Celene; Montero, Ofelia Pérez; Defeo, Omar; Turra, Alexander (Estudos Avançados, 2021)
The complexity of global changes and their effects on social-ecological systems motivate the development of more integrated and innovative management approaches to balance the society-nature relationship. With the challenge of meeting global demands and considering local impacts, Ecosystem-Based Management (EBM) emerges as an assessment and action strategy with the potential to qualify social-ecological interactions. In this sense, sandy beaches are an important and complex social-ecological system whose management has been historically characterized by a reductionist, immediatist, fragmented and technocratic approach – all challenges for EBM implementation. This article aims to discuss opportunities to incorporate EBM in beach management and the challenges to its implementation in Latin America and the Caribbean (LA&C). GBE can guide beach management processes towards achieving sustainability. Despite the challenges faced in LA&C, GBE implementation must be strengthened in the region to support beach sustainability through the promotion of transdisciplinarity and international cooperation.